Design and Conclusions of the Baffin Island Oil Spill Project - Sergy, Gary A.; Blackall, Peter J. (ARCTIC, 1987)
The Baffin Island Oil Spill (BIOS) Project sponsored multidisciplinary field studies between May 1980 and August 1983 in Canada's eastern Arctic at Cape Hatt, on the northern end of Baffin Island. Forty-five cubic metres (45,000 l) of a sweet medium gravity crude oil were released in a typical coastal arctic environment for purposes of scientific investigation. The experimental spills were monitored to quantitatively assess and compare the short- and long-term fate and effects of chemically dispersed oil and a beached oil slick, as well as the effectiveness of shoreline cleanup techniques. Hydrocarbon analyses were carried out on water samples, intertidal sediments, subtidal sediments and macrofaunal tissue. Biological measurements were made on populations of macrophytic algae, benthic infauna and epifauna and microorganisms. Oceanographic, geomorphologic and meteorologic support studies were also performed. The main conclusions of the BIOS Project relate to oil spill countermeasures for arctic nearshore and shoreline areas typified by the experimental site. First, the results offer no compelling ecological reasons to prohibit the use of chemical dispersants on oil slicks in such nearshore areas. Second, the results provide no strong ecological reasons for the cleanup of oil stranded on such shorelines. Thus consideration would be given to the use of chemical dispersants in the nearshore where prevention of shoreline contamination is warranted to protect wildlife or their critical habitat or traditional human land-use sites.Key words: Arctic, marine, oil pollution, oil spill countermeasures, chemically dispersed oil Mots clés: Arctique, milieu marin, pollution par le pétrole, mesures d’intervention contre les déversements de pétrole , pétrole dispersé chimiquement